Pengaruh Platform Ruang GTK dan Komunitas Belajar Terhadap Kompetensi Pedagogik Guru SD Negeri di Kecamatan Todanan Kabupaten Blora - Anora Wanodiya Kurnia; Soedjono Soedjono; Harto Nuroso (Jayapangus Press, 2026)
This study aims to analyze the influence of the Ruang GTK Platform and learning communities on teachers' pedagogical competence, both partially and simultaneously. Previous research generally focuses on improving teacher competence through training or academic supervision, but limited research simultaneously examines the influence of the Ruang GTK Platform and learning communities on teachers' pedagogical competence in the context of public elementary schools at the sub-district level. This study employed a quantitative approach with a survey method. The study population consisted of 308 public elementary school teachers, with a sample size of 174 teachers. The research instruments were tested through validity and reliability tests, while classical assumptions included tests for normality, linearity, multicollinearity, and heteroscedasticity. Data analysis used multiple linear regression, supplemented by t-tests and F-tests. The results indicate that the Ruang GTK Platform has a positive and significant effect on teachers' pedagogical competence. Learning communities also have a positive and significant effect on teachers' pedagogical competence. Simultaneously, the Ruang GTK Platform and learning communities exert a strong influence on improving teachers' pedagogical competence. These findings indicate that utilizing a digital platform for teacher professional development, supported by collaborative activities within a learning community, can strengthen teachers' abilities to plan, implement, and evaluate learning. The implications of this research emphasize the importance of optimizing the use of the Ruang GTK Platform and strengthening teacher learning communities as part of ongoing professional development. Integrating these two approaches can be an effective strategy for systematically, collaboratively, and sustainably improving teachers' pedagogical competence.